The Mother and Child Health Handbook in Japan as a Health Promotion Tool - Jiro Takeuchi MD, PhD; Yu Sakagami MD, PhD; Romana C. Perez BA (SAGE Publishing, 2016)
Background . The Mother and Child Health Handbook (MCHH), a tool used by almost all parents in Japan, serves as a record book shared by parents and health providers to monitor maternal health care throughout the perinatal period, track the child's health and growth, and provide educational information. Methods . A review of the existing literature was performed by narrative review using electronic databases with the search term "Maternal and Child Health Handbook" from January 1980 to February 2016. Results . Twenty-eight papers were obtained: 3 review articles, 17 original articles, 2 brief reports, 2 letters, 1 research note, and 3 proceedings. After the MCHH was initiated in 1947, Japan's infant mortality rate decreased to 2.6 per 1000 live births in 2007, and it is still decreasing. Information recorded in the MCHH at antenatal examinations can be used to evaluate a child's risk of obesity, cardiovascular disease, endocrine disease, mental illness, and infectious disease. Utah's Department of Health implemented a program called "Baby Your Baby" in 1987 based on the Japanese MCHH; this included a similar booklet with family records and educational information. Thus, the MCHH is a unique tool in Japan that has influenced other countries to adopt similar programs. Conclusion . We will confirm the importance of the MCHH's role in promoting health and open dialogue.